AB0835 Association Between Sociodemographic and Clinical Features with Radiographic Severity in Knee Osteoarthritis – Results from Epireumapt. (9th June 2015) - Sepriano, A.R.; Canhão, H.; Rodrigues, A.; Gouveia, N.; Eusébio, M.; Pimentel-Santos, F.; Branco, J.C.
Abstract : Objectives: To assess patient characteristics associated with radiographic severity in knee osteoarthritis (KOA) in a population-based study. Methods: EpiReumaPt is a national epidemiologic, cross-sectional study of rheumatic diseases (RD) in the Portuguese population conducted from September 2011 to December 2013. From the 3877 patients assessed by a rheumatologist on the second phase of the study, we included all cases of KOA defined according to the American College of Rheumatology clinical and/or radiographic classification criteria. Knee x-rays were acquired using a standardized protocol and centrally scored according to the Kellgren-Lawrence (KL) scale. The knee osteoarthritis outcome score (KOOS) was used to assess KOA clinical features. Weighted stepwise multivariate logistic regression was used to assess which features associated with radiographic severity, after stratifying the disease in mild (grade 0 to 2) and severe (grade 3 and 4) KOA according to the KL scale. Results: A total of 981 (weighted prevalence: 12.4%) patients were classified as KOA patients. Knee radiographs were available for 553 patients. From those, 318 (63.7%) had mild disease and 235 (36.3%) had severe disease. On the multivariate analysis, several patient's features were significantly and independently associated to radiographic severity: age (OR: 1.08; p<0.001), obesity (OR: 2.7; p=0.014); dyslipidemia (OR: 2.73; p=0.002), the total number of non-rheumatic comorbidities (OR: 0.63; p<0.001); Country region (OR: 0.61; p<0.001); orthopedic intervention of the knee (OR: 4.71; p=0.004); KOOS symptoms subscale (OR: 0.96; p=0.001; higher KOOS, less symptoms). Alentejo region had the higher proportion of severe disease [56.0% (36.2-75.7)], whereas Lisbon area had the lowest [36.4% (26.9-45.8)]. Conclusions: We found several clinical and sociodemographic features associated with radiographic severity in KOA patients. Our findings contribute to the understanding of disease progression mediators. A longitudinal evaluation is needed to validate these results. Disclosure of Interest: None declared